Modelling and simulation of a single-phase AC-AC matrix converter using Sinusoidal Pulse Width Modulation (SPWM) / Kamarulazhar Daud - Daud, Kamarulazhar (2003)
This paper presents the work carried out in developing computer simulation model using the MATLab/Simulink environment for ac-ac converter. The model for the system is constructed using block diagrams in simulink library and folfills -the characteristics of the system. A direct frequency changer, Single-phase Matrix Converter (SPMC) were used in this work with the output being synthesized using the Sinusoidal Pulse Width Modulation (SPWM) Technique. The circuit is fed from 50V (rms), 50Hz supplying a passive Rand L load. The result obtained is compared with Pspice simulation.